2004
DOI: 10.1159/000072496
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Induces Aberrant Laminin Chain and Collagen Type IV Isotype Expression in the Glomerular Basement Membrane

Abstract: Transforming growth factor-β1 (TGF-β1) contributes to the thickening of the glomerular basement membrane (GBM), abnormal deposition of extracellular matrix (ECM) therein and expansion of the mesangial matrix (MM) in several glomerular kidney diseases. However, the influence of TGF-β1 on the expression of collagen IV isotypes and laminin chains in the GBM and the MM in vivo is not known in detail. By using transgenic mice with TGF-β1 expression targeted to the juxtaglomerular apparatus and a combination of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
3
25
0
1
Order By: Relevance
“…Consistent with an elevation of ECM synthesis pathways, we also observed increased expression of the collagen genes Col1A1, Col1A2, Col3A1, Col4A1 and Col4A2. It is of particular interest to note that increased TGF-β signaling in vivo has previously been shown to induce aberrant collagen type IV isotype (4A1 and 4A2) synthesis in the glomerular basement membrane of the kidney [26]. We also observed increased expression of the versican gene in nephrotic samples.…”
Section: Resultssupporting
confidence: 57%
“…Consistent with an elevation of ECM synthesis pathways, we also observed increased expression of the collagen genes Col1A1, Col1A2, Col3A1, Col4A1 and Col4A2. It is of particular interest to note that increased TGF-β signaling in vivo has previously been shown to induce aberrant collagen type IV isotype (4A1 and 4A2) synthesis in the glomerular basement membrane of the kidney [26]. We also observed increased expression of the versican gene in nephrotic samples.…”
Section: Resultssupporting
confidence: 57%
“…Interestingly, during infection and inflammation, TGF␤1 has specifically been shown to induce an aberrant laminin ␤1 chain expression in the kidney (12). We also found that nucleosomes associated only with laminins containing the ␤1 chain in the GBM and in the mesangial matrix of patients with lupus nephritis, which led us to hypothesize that local TGF␤1 may play an important role in the pathogenesis of lupus nephritis.…”
mentioning
confidence: 65%
“…This feature has also been demonstrated experimentally using TGF␤1-transgenic animals (12,22). Bioactive TGF may derive from the circulation, the juxtaglomerular apparatus, or the glomerular cells themselves during infections and inflammation (30,31).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations